Catheter-Based Endomyocardial Delivery of Mesenchymal Precursor Cells Using 3D Echo Guidance Improves Cardiac Function in a Chronic Myocardial Injury Ovine Model. Issue 12 (December 2013) - Cheng, Yanping; Yi, Genghua; Conditt, Gerard B.; Sheehy, Alexander; Kolodgie, Frank D.; Tellez, Armando; Polyakov, Igor; Gu, Anguo; Aboodi, Michael S.; Wallace-Bradley, David; Schuster, Michael; Martens, Timothy; et al.
The administration of bone marrow-derived stem cells may provide a new treatment option for patients with heart failure. Transcatheter cell injection may require multi-imaging modalities to optimize delivery. This study sought to evaluate whether endomyocardial injection of mesenchymal precursor cells (MPCs) could be guided by real-time 3D echocardiography (RT3DE) in treating chronic, postinfarction (MI) left ventricular (LV) dysfunction in sheep. Four weeks after induction of an anterior wall myocardial infarction in 39 sheep, allogeneic MPCs in doses of either 25 × 10 6 ( n = 10), 75 × 10 6 ( n = 9), or 225 × 10 6 ( n = 10) cells or nonconditioned control media ( n = 10) were administered intramyocardially into infarct and border zone areas using a catheter designed for combined fluoroscopic and RT3DE-guided injections. LV function was assessed before and after injection. Infarct dimension and vascular density were evaluated histologically. RT3DE-guided injection procedures were safe. Compared to controls, the highest dose MPC treatment led to increments in ejection fraction (3±3% in 225M MPCs vs. −5±4% in the control group, p < 0.01) and wall thickening in both infarct (4±4% in 225M MPCs vs. −3±6% in the control group, p = 0.02) and border zones (4±6% in 225M MPCs vs. −8±9% in the control group, p = 0.01). Histology analysis demonstrated significantly higher arteriole density in the infarct and border zones in the highest dose MPC-treated animals compared to the lower dose or control groups. Endomyocardial implantation of MPCs under RT3DE guidance was safe and without observed logistical obstacles. Significant increases in LV performance (ejection fraction and wall thickening) and neovascularization resulted from this technique, and so this technique has important implications for treating patients with postischemic LV dysfunction.